Experimental Investigation of Heat Transfer in a Flat-wall Impinging Diesel Spray Flame under Diesel-like Conditions - Safiullah Safiullah; Samir Chandra Ray; Iis Rohmawati; Rizal Mahmud (Journal of Mechanical Engineering, Science, and Innovation, 2023)
The heat loss through the walls of Internal Combustion Engines (ICEs) needs to be minimized and improved since it has a detrimental impact on the overall thermal efficiency of the engine. This study focuses on investigating heat transfer in a flat-wall impinging diesel spray flame, simulating diesel conditions, to optimize engine parameters. The effects of factors such as various injection pressures, nozzle hole diameters, impingement distances, and oxygen concentrations are analysed in combined and individually. Experimental techniques, such as high-speed imaging, heat flux sensors, and thermocouples, are used to visualize spray flame, measure heat flux profiles and temperature distributions, respectively. Preliminary results and their implications on heat transfer and heat loss are discussed. Regarding the parametric studies investigating the effect on wall heat loss under conditions similar to those of a small diesel engine, it was observed that the transferred heat on the wall was significant in certain conditions. These results emphasize the effectiveness of manipulating the injection rate profile as a viable step to suppress the heat transfer through the wall.